2019
DOI: 10.1177/2397002219892197
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and work engagement: Exploring explanatory mechanisms

Abstract: Construct proliferation in the leadership field raises questions concerning parsimony and whether we should focus on joint mechanisms of leadership styles, rather than the differences between them. In this theoretical research article, we propose that positive leadership styles translate into similar leader behaviors on the work floor that influence employee work engagement through a number of shared pathways. We take a deductive approach and review several established theories as well as relevant up-to-date e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
161
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(185 citation statements)
references
References 130 publications
10
161
1
13
Order By: Relevance
“…The current study uncovered that academician engagement is positively connected to turnover intention (Oruh et al, 2019;Gadi & Kee, 2020). Given these outcomes, scholars have suggested the need to focused on avenues to enhance individual engagement (Decuypere & Schaufeli, 2019). To unearth the assumptions of engagement, the likelihood that the correlation linking engagement and turnover intention changes as an act of a moderating construct needs to be researched in the Nigerian context.…”
Section: R E S E a R C H O B J E C T I V E Smentioning
confidence: 93%
“…The current study uncovered that academician engagement is positively connected to turnover intention (Oruh et al, 2019;Gadi & Kee, 2020). Given these outcomes, scholars have suggested the need to focused on avenues to enhance individual engagement (Decuypere & Schaufeli, 2019). To unearth the assumptions of engagement, the likelihood that the correlation linking engagement and turnover intention changes as an act of a moderating construct needs to be researched in the Nigerian context.…”
Section: R E S E a R C H O B J E C T I V E Smentioning
confidence: 93%
“…Leaders are important agents to nurture and manage work engagement among their employees. A recent meta‐analysis found that various leadership styles are positively related to work engagement, such as ethical leadership ( k = 9; ρ = .58), transformational leadership ( k = 36; ρ = .46), servant leadership ( k = 3; ρ = .43), authentic leadership ( k = 17; ρ = .38), and empowering leadership ( k = 4; ρ = .35) (DeCuypere & Schaufeli, ). Although these leadership styles are related to work engagement, in‐depth knowledge about the underlying mechanism is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholder's involvement and active participation is also a key factor for employee engagement, since being part of the organization strategy and narrative helps the employee identification and feeling of belonging, which are important intangible assets for all kinds of organizations. Employee engagement is positively linked to better performance, higher customer loyalty, well-being and lower turnover (Decuypere and Schaufeli, 2020). Gallup (2017) shows that engaged faculty and staff members are critical to student success, since being emotionally and psychologically committed to their work helps students overcome the difficulties and anxiety they face.…”
Section: Employee Engagementmentioning
confidence: 99%